Aquatic Exercise Is Effective in Improving Exercise Performance in Patients with Heart Failure and Type 2 Diabetes Mellitus. (23rd April 2012) - Åsa, Cider; Maria, Schaufelberger; Katharina, Stibrant Sunnerhagen; Bert, Andersson
Abstract : Background . Peak oxygen uptake (VO 2peak ) and muscle function are more decreased in patients with a combination of chronic heart failure (CHF) and type 2 diabetes mellitus (2DM) compared to patients with only one of the conditions. Further, patients with 2DM have peripheral complications that hamper many types of conventional exercises. Aim . To evaluate the efficacy and applicability of eight-week aquatic exercise in patients with the combination of CHF and 2DM. Methods . Twenty patients (four women) with both CHF and 2DM (age 67.4 ± 7.1, NYHA II-III) were randomly assigned to either aquatic exercise or a control group. The patients exercised for 45 minutes 3 times/week in 33–34 ° C, swimming pool. Results . The training programme was well tolerated. Work rate (+ 11.7 ± 6.6 versus − 6.4 ± 8.1  watt, P < 0.001 ) and VO 2peak (+ 2.1 ± 0.8 versus − 0.9 ± 1.4 mL⋅kg −1 ⋅min −1, P < 0.001 ) and walking capacity (P = 0.01 ) increased significantly in the training group. Muscle function was also significantly improved and Hba1c decreased significantly (P < 0.01 ) during training, while fasting glucose, insulin, c-peptide, and lipids were unchanged . Training also increased vitality measured by SF-36 significantly (P = 0.05 ). Conclusion . Aquatic exercise could be used to improve exercise capacity and muscle function in patients with the combination of CHF and 2DM.